Secure data transmission towards mitigating potentially unknown threats in wireless sensor network - Puttaswamy, Chaya; Kanakapura Shivaprasad, Nandini Prasad (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Wireless sensor network (WSN) is known for its wider range of applications towards sensing physical attributes over human-inaccessible regions. With consistently rising concerns of security threats, WSN is the pivotal topic of network security. A literature review showcases the shortcomings of conventional data transmission schemes in WSN. This manuscript introduces an innovative approach to mitigating the potentially vulnerable and unknown threats. The implemented model promotes a group-based communication followed by a newly introduced threat onlooker node capable of identifying the malicious request of a newly designed adversary module. The scheme also hybridizes symmetric and asymmetric encryption at the end to cipher the aggregated data. The validation of the model is carried out considering standard scores of simulation parameters related to system variables. Further, the scheme has been compared with frequently adopted real-world encryption algorithms. Scripted in MATLAB, the model is assessed to confirm 35% of increased residual energy, 57% of better threat detection, 27% of enhanced throughput, and 68% of reduced processing time in contrast to existing secure data transmission schemes.